2011
DOI: 10.1523/jneurosci.0529-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

The Diabetes Drug Liraglutide Prevents Degenerative Processes in a Mouse Model of Alzheimer's Disease

Abstract: Type 2 diabetes is a risk factor for Alzheimer's disease, most likely linked to an impairment of insulin signaling in the brain. The incretin hormone glucagon-like peptide-1 (GLP-1) facilitates insulin signaling, and novel long-lasting GLP-1 analogs, such as liraglutide, are on the market as diabetes therapeutics. GLP-1 has been shown to have neuroprotective properties in vitro and in vivo. Here we tested the effects of peripherally injected liraglutide in an Alzheimer mouse model, APP swe /PS1 ⌬E9 (APP/PS1). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
474
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 586 publications
(498 citation statements)
references
References 34 publications
22
474
0
2
Order By: Relevance
“…Similarly, treatment of patients with type 2 diabetes and islet recipients with type 1 diabetes, at early stages of beta cell dysfunction may slow down the process of hIAPP aggregation and thereby amyloid-induced beta cell death. In support, two recent studies have demonstrated that treatment with GLP-1R agonists, such as exenatide and liraglutide, reduces Aβ oligomers, amyloid plaque formation and toxicity in the brains of mice in models of Alzheimer's disease [47,48].…”
Section: Discussionmentioning
confidence: 78%
“…Similarly, treatment of patients with type 2 diabetes and islet recipients with type 1 diabetes, at early stages of beta cell dysfunction may slow down the process of hIAPP aggregation and thereby amyloid-induced beta cell death. In support, two recent studies have demonstrated that treatment with GLP-1R agonists, such as exenatide and liraglutide, reduces Aβ oligomers, amyloid plaque formation and toxicity in the brains of mice in models of Alzheimer's disease [47,48].…”
Section: Discussionmentioning
confidence: 78%
“…In contrast, insulin deficiency has been shown to accelerate amyloidogenic pathology in a mouse model of AD [119]. In addition to direct insulin administration, compounds that can promote insulin secretion, such as glucagon-like peptide 1 (GLP-1) analogues, are being actively investigated., Liraglutide and Val(8)GLP-1, GLP-1 analogues, were found to be neuroprotective, rescue long-term potentiation and memory deficits, and reduce plaque loads in an AD mouse model [121][122][123]. Peripherally injected liraglutide and another GLP-1 analogue, lixisenatide, penetrated the BBB and promoted neurogenesis [124].…”
Section: Anti-diabetes Drugsmentioning
confidence: 99%
“…Also, sitagliptin, saxagliptin and vildagliptin showed anti‐inflammatory properties77, 78, 79, as well as liraglutide in a late‐stage AD rodent model75. Moreover, peripherally‐administered liraglutide and D‐Ala 2 GIP increased neuronal progenitor cell proliferation and neurogenesis in AD rodent models72, 75, 83.…”
Section: Type 2 Diabetes Mellitus Dementia and Incretin‐based Therapiesmentioning
confidence: 99%
“…However, two other studies reported no reduction of both APP and Aβ levels, despite the fact that treatment did have beneficial effects on memory or LTP82, 86. Peripherally‐administered liraglutide reduced both Aβ and APP levels72, even in a late‐stage AD rodent model75. Furthermore, peripherally‐administered sitagliptin, saxagliptin and vildagliptin lowered the levels of Aβ77, 78, 79.…”
Section: Type 2 Diabetes Mellitus Dementia and Incretin‐based Therapiesmentioning
confidence: 99%